Molecular, biological, and morphometric comparisons between different geographical populations of Rhipicephalus sanguineus sensu lato (Acari: Ixodidae) - Sanches, Gustavo S. [UNESP]; Évora, Patrícia M. [UNESP]; Mangold, Atílio J.; Jittapalapong, Sattaporn; Rodriguez-Mallon, Alina; Guzmán, Pedro E.E.; Bechara, Gervásio H. [UNESP]; Camargo-Mathias, Maria I. (Elsevier, 2016)
In this study, different geographical populations of Rhipicephalus sanguineus sensu lato were compared by molecular, biological, and morphometric methods. Phylogenetic trees were constructed using 12S and 16S rDNA sequences and showed two distinct clades: one composed of ticks from Brazil (Jaboticabal, SP), Cuba (Havana) Thailand (Bangkok) and the so-called tropical strain ticks. The second clade was composed of ticks from Spain (Zaragoza), Argentina (Rafaela, Santa Fe) and the so-called temperate strain ticks. Morphometric analysis showed good separation between females of the two clades and within the temperate clade. Males also exhibited separation between the two clades, but with some overlap. Multiple biological parameters revealed differences between the two clades, especially the weight of the engorged female. These results confirm the existence of at least two species under the name R. sanguineus.
Keywords: Genetic analysis; Morphometry; Rhipicephalus sanguineus; Taxonomy